53 interesting ways to communicate your research - Daly, Irenee; Haney, Aoife Brophy (Professional and Higher Partnership, 2014)
To maximise the value of your research, you need to communicate it to others. There are many ways to do so: examples include applications and bids for funding, conference presentations, gray literature, journal papers, media (old and new), public talks, and teaching. This book provides fresh, creative, ways of making the most of these and other opportunities. It provides 53 practical suggestions, each based on ideas tried and tested by the contributors.